Venture governance, CEO duality, and new venture performance - Li, Mingxiang; Cao, Zhi; Terjesen, Siri (Strategic Entrepreneurship Journal, 2024)
Abstract Research summary How a new venture improves performance when facing both principal and agency problems is an important yet understudied question. This study examines the effectiveness of CEO duality in mitigating the principal problem and enhancing entrepreneurial success. By granting more power to CEOs, CEO duality can alleviate the principal problem; however, CEO duality may simultaneously exacerbate CEOs' agency problems. Using manually collected panel data on 1403 newly established U.S. commercial banks, we find a positive relationship between CEO duality and new venture performance. The CEO duality–new venture performance relationship strengthens when CEOs are also founders of their firms and weakens when the share of corporate ownership reflects heavy investment by incumbent firms. Our findings highlight that venture governance needs to address principal and agency problems simultaneously. Managerial summary Large corporations typically face agency problems due to the separation of ownership and control such that managers do not act in the best interests of owners. New ventures tend to experience fewer agency problems because owners/principals are also likely to be managers/agents. New ventures often face severe principal problems due to directors' potential conflict of interests such as investments in rival companies. Our study suggests that new ventures can mitigate principal problems by appointing a CEO as the chair of the board of directors. Our longitudinal analysis of new U.S. commercial banks finds that this dual CEO‐chair structure leads to better performance. This relationship strengthens in the case of founder‐CEOs and weakens among new banks co‐founded by other large bank holding companies.